Managerial accounting : creating value in a dynamic business environment - Hilton, Ronald W. (McGraw-Hill Irwin, 2009)
Focuses on teaching students to use accounting information to manage an organization. This title covers topics such as activity-based costing, target costing, the value chain, customer profitability analysis, and throughput costing. It also includes traditional topics such as job-order costing, budgeting and performance evaluation.